The Role of Labor Market Institutions in the Great Recession - Merkl, Christian; Lechthaler, Wolfgang; Boysen-Hogrefe, Jens; Groll, Dominik (Applied Economics Quarterly, 2010)
The recent Great Recession had very heterogeneous effects on the labor market outcomes in industrialized countries. We analyze the role of three labor market institutions in this context, namely the level of firing costs, the existence of short-time work and the wage formation process. This paper combines two different perspectives, a structural dynamic model perspective and an empirical cross-country perspective. Using the Lechthaler, Merkl, and Snower (2010) model, we first simulate the effects of the three labor market institutions during a recession. Using the panel of the EU-15 countries without Luxembourg, we then test the predictions of the model. Indeed, we find evidence that the three labor market institutions can partially explain the different labor market reactions across countries during the Great Recession. However, further empirical research is needed, as more data can be expected to become available, especially with respect to the use of short-time work in different countries.
WiSo-Import:2015-03-26:1142
Keywords: unit labor costs; Transformation; short-time work; Forschungsbericht 2010; firing costs; Employment